FUNCTIONAL LOW FAT CHICKEN MEAT BALLS ENRICHED WITH GRAPE (VITIS VINIFERA) POMACE POWDER - D, Santhi; A, Kalaikannan; A, Elango (Journal of Meat Science, 2023)
This study was conducted to prepare low fat chicken meat balls with incorporation of grape (Vitis vinifera) pomace powder and assess its proximate composition, physico-chemical, sensory and textural properties. Emulsion based low fat chicken meat balls were prepared with the addition of grape pomace powder (GPP) at  levels of 2%, 4% and 6%, over and above the amount of meat along with a control. There was a significant (P≤0.05) increase in the crude fibre, total ash and gross energy levels of the meat balls at 4% and 6% level of inclusion of GPP.  In the physico-chemical properties, the emulsion pH and product pH significantly (P≤0.05) decreased with increase in the GPP content. In sensory evaluation, the scores for appearance and colour, flavour, juiciness, tenderness and overall acceptability were significantly (P≤0.01) reduced for the 6% GPP treatment. Though the scores of 2% and 4% treatments were significantly (P≤0.05) lower than that of the control, the scores were above the acceptable level. The textural properties of the chicken meat balls significantly  (P≤0.05) changed with the addition of GPP. It is concluded emulsion based functional low fat chicken meat balls could be enriched with an optimum level of 4% of grape pomace powder without much affecting the quality characteristics, thus enhancing the dietary fibre content and antioxidant efficacy of the chicken meat balls.
Keywords: Chicken meat balls; Grape pomace powder; Dietary fibre; Proximate composition; Physico-chemical properties; Sensory Properties; Textural properties